Lithuania’s Binary Worker Classification Vs. A Teleological Interpretation of the EU’s ‘Worker’ Concept by Germany and the UK - Lauschke Hans (Baltic Journal of Law & Politics)
The article explores whether Lithuania’s concept of darbuotojas (employee) and its rigid binary classification of work relationships is challenged by an evolving European employment law landscape, shaped by a rise of unconventional work relationships that blur the lines between employees and self-employed persons. This issue is examined in light of varying interpretations of the EU’s ‘worker’ concept(s) in the United Kingdom (UK) and Germany, where courts increasingly extend protections to individuals in atypical employment forms by broadly (re-)interpreting traditional terms. Additionally, their domestic systems recognize intermediate categories between employees and self-employed persons, such as arbeitnehmerähnliche Personen (employee-like persons) in Germany or the UK’s ‘limb (b) workers’, aiming to provide certain protection for a wider group of working individuals. These approaches influence both countries’ understanding of an autonomous EU ‘worker’ concept, particularly evident in connection with Council Directive 89/391/EEC, which introduced measures to enhance the safety and health of workers at work and was adopted more than 30 years ago.